Workshop Penulisan Soal Objektif dan Valid Berorientasi Higher Order Thinking Skills - Syamsinar, Syamsinar; Rumite, Wayan; Ikram, Muhammad; Buhati Asfyra, Intan; Nur Sa'diyyah, Fadhilah (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
This Community Service activity aims to improve mathematics teachers' competency in developing valid objective questions oriented toward Higher Order Thinking Skills (HOTS). The activity was conducted at SMAN 1 Wondama, using a participatory and contextual mentoring approach. The main challenge faced by the partner school was teachers' limited understanding of how to design assessment instruments that systematically measure students' higher-order thinking skills and align with the characteristics of mathematics learning. The activity's implementation methods included needs analysis, reinforcement of HOTS concepts, assistance in developing questions, and joint evaluation and reflection. The results of the activity showed an increase in teachers' understanding and skills in developing HOTS questions, demonstrated by the development of example objective questions at levels C4 to C6 with contextual stimuli and clear indicators. This activity resulted in the development of question writing guidelines and examples of HOTS questions ready for use in learning. Thus, this community service activity directly contributed to improving the quality of mathematics assessment and learning at the partner school.